The Impact of Job Satisfaction and Performance on User Satisfaction with Banking Services - Jocelyne Jia Lin Lee; Lyn Liq Ooi; Xiang Yang Wun; Pei Wen Wong; Jia Yue Yin; Hai Hong Yang; Daisy Mui Hung Kee (International Journal of Tourism and Hospitality in Asia Pasific, 2024)
This study examines the relationships between customer service quality, employee job satisfaction, job performance, and user satisfaction in the banking industry, with a focus on Maybank. The objective is to determine how employee satisfaction and performance impact user satisfaction and customer service experience. A survey was conducted among 200 Malaysian banking customers, and responses were analyzed using regression analysis to test six hypotheses. The results confirm that customer service experience, employee job satisfaction, and job performance all significantly influence user satisfaction. Specifically, customer service experience (? = 0.291, p 0.01) and employee job satisfaction (? = 0.322, p 0.001) show strong positive effects on user satisfaction, while employee job performance (? = 0.200, p 0.05) also contributes positively. Additionally, employee job satisfaction significantly enhances both job performance (? = 0.732, p 0.01) and customer service experience (? = 0.340, p 0.01). Employee performance is a key factor in delivering superior customer experiences (? = 0.534, p 0.001). The study concludes that improving employee satisfaction is crucial for boosting job performance and customer service, which in turn elevates user satisfaction.